The effect of a floating conductor on the breakdown performance of a non-uniform air gap under HVDC stress at both polarities - Hart, Craig L (My University, 2013)
A model for predicting the e ect of a Floating Conductor (FC) on the breakdown voltage is presented and critically analysed in conjunction with results from laborat- ory work. Firstly, the scenario of live-line maintenance on HVDC lines is modelled by a FC within a rod-plane gap. The use of a rod-plane gap is to produce a non- uniform eld distribution, representing the non-uniform eld that would surround the conductor of a transmission line. This test object is then further simpli ed into simple gap geometries such that the breakdown voltage of the two gaps separated by the FC can be numerically calculated and the breakdown voltage of the entire test object predicted. The DC breakdown voltage of the rod-plane gap is then presented as a function of the position of the FC in the gap. The simulations are performed for both positive and negative DC voltages. The laboratory work uses a similar test object, with the U50 breakdown voltage recorded as a function of the position of the FC within the rod-plane gap. The simulation model is then critically analysed by comparing the laboratory and simulation results. It is concluded that although the model predicts the change in the breakdown strength from the starting to the ending points, the developed model has omitted detail that leads to discrepancies in the predicted results when compared to the laboratory results. This omitted detail includes the e ect of corona discharge from the FC, additional parameters a ecting the potential of the FC, the oversimpli cation of the gap geometry for numerical calculation, and the lack of a dynamic model for the changing electrostatic scenario as an applied voltage increases towards the breakdown voltage. The results also show that the position of a FC a ects the breakdown strength of a non-uniform gap. This e ect is due to the polarity dependent nature of breakdown in a non-uniform gap and in particular, the di erence in the breakdown strength of a quasi-symmetrical (rod-rod) and asymmetrical (rod-plane) non-uniform gap. The e ects of charged particles and their interaction with the oating conductor in the gap is also deemed to have a signi cant e ect on the breakdown strength, with their behaviour also in uenced by the sustained electric eld that is a result of HVDC stress.